2016
DOI: 10.1039/c6ob00561f
|View full text |Cite
|
Sign up to set email alerts
|

Reversible and formaldehyde-mediated covalent binding of a bis-amino mitoxantrone analogue to DNA

Abstract: Collins, J. (2016). Reversible and formaldehyde-mediated covalent binding of a bis-amino mitoxantrone analogue to DNA. Organic and Biomolecular Chemistry, 14 (20), 4728-4738. Reversible and formaldehyde-mediated covalent binding of a bis-amino mitoxantrone analogue to DNA AbstractThe ability of a bis-amino mitoxantrone anticancer drug (named WEHI-150) to form covalent adducts with DNA, after activation by formaldehyde, has been studied by electrospray ionisation mass spectrometry and HPLC. Mass spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The molecular modelling investigations were carried out using HyperChem Release 7.5 software as previously described. 10 Duplex B-DNA was generated from the nucleic acid database. Energy restraints were added to maintain the H-bonds as expected in duplex DNA during the optimisation procedures.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The molecular modelling investigations were carried out using HyperChem Release 7.5 software as previously described. 10 Duplex B-DNA was generated from the nucleic acid database. Energy restraints were added to maintain the H-bonds as expected in duplex DNA during the optimisation procedures.…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence WEHI-150 can more rapidly and more extensively form covalent adducts with DNA than mitoxantrone. 10 In order to further develop the anthracenedione class of anticancer drugs it is important to determine the structure of a mitoxantrone-or mitoxantrone derivative-DNA adduct. Previous studies have demonstrated that WEHI-150 preferentially intercalates and then forms covalent adducts with DNA at CpG sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously synthesized and utilized the indolo [1,2-b] [2,7]naphthyridine-5,12-dione (6) ring system to forge several members of the 6H-pyrido [4,3-b]carbazole family of antitumor alkaloids, including ellipticine (7), 9-methoxyellipticine (8), olivacine (9), 13-oxoellipticine (10), 7,8,9,10-tetrafluoroellipticine (11), and ellipticine quinone (12) [15][16][17][18][19][20] (Figure 2). A variation of our method allowed for the synthesis of 10Hpyrido [2,3-b]carbazoles (13) 21 and 6,11-disubstituted-benzo[b]carbazoles (14). 22 The shape similarity of quinone (6) with that of ellipticine quinone (12) and calothrixin B (15), both of which display antitumor activity, [23][24][25] suggested that it would be fruitful to examine indoloquinone 6 and its amino-substituted derivatives for DNA binding, given the known enhancement of DNA binding and resulting biological activity imparted by the alkylamino side chains in antitumor quinones 2-5.…”
Section: Figurementioning
confidence: 99%
“…The antitumor activity and DNA affinity of amino-substituted quinones is well established, [1][2][3][4] and several drugs in this category have seen utility in the cancer clinic; for example, mitomycin (1), 5,6 ametantrone (2), 7 mitoxantrone (3), 8,9 pixantrone (4), [10][11][12] and WEHI-150 (5) 13,14 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%